Histomorphology of the hypothalamo-neurosecretory system of the endangered golden mahseer, Torputitora (Hamilton-Buchanan) - Pandey, A K; LaL, K K; Mahanta, P C (Indian Journal of Fisheries, 2011)
Hypothalamus of Tor putitora consist mainly of nucleus preopticus (NPO), nucleus laterlais tuberis (NLT) and their axonal tracts. NPO is a paired structure topographically located on either side of the third ventricle anterodorsal to the optic chiasma. Based on size of the neurosecretory cells, NPO is morphologically distinguishable into dorsal pars magnocellularis (PMC) comprising larger neuronal cells whereas ventrally situated pars parvocellularis (PPG) is formed of smaller cells. NPO neuronal cells were positive (+) to aldehyde fuchsin (AP) and CAHP but they were also stainable with acid fuchsin in Mallory’s triple stain. A few acid fuchsin +ve neurosecretory globules were also encountered in NPO. NLT neurosecretory cells were large, pleomorphic and distributed uniformly at the floor of the brain close to the infundibulum. They stained readily with acid fuchsin. Herring bodies (HB) were not observed in the hypothalamo-neurohypophysis of the golden mahseer